A Modeling Study of the Cycling Behavior of Non-Aqueous Li-O2/CO2 Batteries. Issue 2 (10th February 2021) - Wang, Yuanhui; Hao, Liang; Bai, Minlin
Abstract : A non-aqueous lithium-oxygen/carbon dioxide (Li-O2 /CO2 ) battery model is developed with the consideration of lithium peroxide (Li2 O2 ) and lithium carbonated (Li2 CO3 ) depositions during the discharge-charge cycles. By comparing with Li-O2 batteries, the presence of CO2 increases the discharge voltage and capacity at a not very high current density. The effects of transport properties of O2 and CO2 in the electrolyte on the battery cycling performance are explored. The increases of diffusivity and solubility of O2 are beneficial to increase the battery capacity but worsen the cycling capacity decay. Conversely, the increase of CO2 diffusivity promotes the battery capacity and weakens the capacity loss with cycling. The solubility of CO2 plays a more complicated role than CO2 diffusivity on the cycling performance of Li-O2 /CO2 batteries. A moderate CO2 solubility leads to the most severe decay of the capacity with cycles, but an enough higher CO2 solubility qualifies the battery a much better reversible capacity. These results present that the capacity decay of Li-O2 /CO2 batteries with cycles is primarily determined by the accumulation of undecomposed Li2 CO3 near the cathode outer boundary. Therefore, the promotion of Li2 CO3 decomposition near the cathode outer boundary is critical to improving the Li-O2 /CO2 battery's cycling performance.